PENGGUNAAN METODE GEOLISTRIK RESISTIVITAS 3-DIMENSI UNTUK MENGETAHUI SEBARAN LIMBAH DI TPA JATIBARANG KOTA SEMARANG - Aspia Prapitari; Tony Yulianto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
The waste distribution in TPA of Jatibarang in Semarang has measured and interpreted using resistivity geoelectric 3-D method with pole – pole configuration.Field data has processed using Res3dinv program which gives horizontal and vertical cross section as the result. The result of res3dinv is entered to RockWork software to obtain 3-D cross section. The result of RockWork software could describe the waste distribution in TPA of Jatibarang.The research result shows that the direction of waste distribution in TPA of Jatibarang which has resistivity range 21,5 Ωm – 39,2 Ωm is to East – South which is to Kreo river. Key words : Resistivity geoelectric 3-D, Garbage dump waste, Pole – pole configuration, Res3dinv, RockWork